Keanekaragaman Makroarthropoda Tanah di Lahan Persawahan Padi Organik dan Anorganik, Desa Bakalrejo Kecamatan Susukan Kabupaten Semarang - Witriyanto, Roma; Hadi, Mochamad; Rahadian, Rully (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
Inorganic paddies system has a negative impact as pests become resistant, environmental pollution and residual hazard. People who are aware of the impact of the application of synthetic chemicals have been applying organic farming. This research aimed to compare the abundance, diversity and dominance of soil macroarthropodsÂ in the organic and inorganic paddies field in Village Bakalrejo, Susukan District of Kabupaten Semarang. Sampling of soil macroarthropods method used pit fall traps . Fifteen pit fall traps were set up in the research area and they were divided into three line whith respective line are 5 pit fall traps. Soil macroarthropods Â which has been found were identified up to family taxon. The results of the research shows abundance of soil macroarthropods organic rice in paddy fields higher (297) than in inorganic paddy fields (236). Diversity of soil macroarthropods in every phase of rice growth (vegetative, reproductive, ripening and post-harvest) was higher in organic paddy fields (1,479; 1,644; 1,561; 1,019) than inorganic paddy fields (1.391; 0.595; 1.286; 1.002). Based on the relative abundance index, soil macroarthropods family dominated organic paddy fields in every phase of rice growth (vegetative, reproductive, ripening, and post-harvest) was lower (Gryllidae: 39.4%; Carabidae: 46.7%; Formicidae: 44.1 %; Formicidae: 48.8%) than in the inorganic paddy fields (Carabidae: 35.5%; Carabidae: 57.4%; Formicidae: 56.3%; Formicidae: 77.6%). Key words :Â biodiversity, soil macroarthropods, organic farming.